An Evaluation of Tax Digitalization Efforts by Federal Inland Revenue Service and their Impacts on Tax Collection 2002-2021 - Sani Damamisau Mohammed; Abdulsalam Mas'ud; Yusuf Ibrahim Karaye; Muhammad Muhammad Sallau; Aishatu Danjuma Adam; Bashir Ali Sulaiman (Journal of Accounting and Taxation, 2023)
The federating states and capital of federal republic of Nigeria are too dependent on federally collected revenues largely from oil and gas. However, taxation is indisputably the most viable and sustainable means of raising revenue for public expenditures. Therefore, the federal government can enhance its bases of taxation to generate more tax revenue for the federating units to share especially with known shocks in oil and gas revenue. Conversely, increasing number of individuals and corporate bodies that pay taxes to the federal government are making tax administration more difficult. To overcome this, the Federal Inland Revenue Service (FIRS) has embarked on processes of digitizing tax administration at the federal level. Consequently, the aim of this study is to evaluate the impact of the tax digitalization processes by FIRS by one, describing the digitalizations and two, by undertaking trend analyses of total tax revenue collections 2002-2021. To achieve these, secondary data is collected from the literature and publications of the FIRS while public policy analytical framework underpins the study. Results from the study revealed that there are consistencies in efforts by the FIRS to digitalize tax administration in Nigeria even though implemented in short time intervals. Similarly, on the overall, there are increasing but fluctuating trends of tax revenue collection by FIRS 2002-2021 implying the positive impacts of the current digitalization efforts.